(untitled) (Marketing Journal, 2026)
Abstract This article analysed value creation processes and the application of relationship marketing theory in the B2B market of textile industry enterprises. The study systematically examined relational, added, and strategic levels of value. Key elements of the conceptual models developed by Dwyer–Schurr–Oh, Morgan–Hunt, and Ulaga– Eggert were adapted to the textile sector. The stages of B2B relationship development were identified, and the influence of trust, commitment, and information exchange on value formation was evaluated. Based on the analysis of Uzbekistan’s textile industry export activity and international cooperation practices, directions for strengthening relationship capital were outlined. The research results were assessed as a practical basis for strengthening strategic partnerships and developing value-oriented B2B relationships in textile enterprises. Keywords: relationship marketing, B2B market, value creation, textile industry, strategic partnership, trust, integration model.